2017
DOI: 10.2147/nsa.s129468
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial surfactant competition and its impact on poly(ethylene oxide)/Au and poly(ethylene oxide)/Ag nanocomposite properties

Abstract: The structure and properties of nanocomposites of poly(ethylene oxide), with Ag and Au nanoparticles, surface modified with a 1:1 (by volume) oleylamine/oleic acid mixture, were investigated via transmission electron microscopy, scanning electron microscopy, thermogravimetric analysis, differential scanning calorimetry (DSC), infrared spectroscopy, dynamic mechanical analysis, and static mechanical testing. Results indicated that there was more oleylamine on Ag nanoparticles but more oleic acid on Au nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…The TGA was used for quantitative analysis to determine both organic and inorganic phases. The TGA profile of pure oleic acid typically exhibited single-step thermal degradation with the maximum rate at around 280°C as several studies reported in the literature [22][23][24]. In the present work, the TGA was carried out in the range of room temperature to 600°C in an inert atmosphere with a heating rate of 10°C/min.…”
Section: Tga Of Organic Ferrofluid and Magnetic Emulsionmentioning
confidence: 78%
“…The TGA was used for quantitative analysis to determine both organic and inorganic phases. The TGA profile of pure oleic acid typically exhibited single-step thermal degradation with the maximum rate at around 280°C as several studies reported in the literature [22][23][24]. In the present work, the TGA was carried out in the range of room temperature to 600°C in an inert atmosphere with a heating rate of 10°C/min.…”
Section: Tga Of Organic Ferrofluid and Magnetic Emulsionmentioning
confidence: 78%
“…The broad peak at 543 K and the less intense peak at 673 K are most probably attributed to the degradation of the organic surfactants [ 40 ], which have the ability to bind to the surface of the seeds to prevent their aggregation. In this range of temperatures, the major loss of weight (~4%) is observed, as can be seen in the TGA signal.…”
Section: Resultsmentioning
confidence: 99%
“…The seeds were heated from room temperature to 1273 K. During the heating process from room temperature to 800 K, two peaks in the DTA curve were observed, associated to two weight losses in the TGA curve. The broad peak at 543 K and the less intense peak at 673 K are most probably attributed to the degradation of the organic surfactants [40], which have the ability to bind to the surface of the seeds to prevent their aggregation. In this range of temperatures, the major loss of weight (~4%) is observed, as can be seen in the TGA signal.…”
Section: Characterizations Of the Nanocrystalsmentioning
confidence: 99%
“…These results were confirmed from the higher RS % (Table 1) of CaCO 3 −OA than CaCO 3 −EOA values. The silver NPs showed different thermal degradation thermograms (Figure 6c,d) than those obtained with CaCO 3 NPs (Figure 6a,b) due to using complex mixture of unsaturated fatty acid with OAm for preparing hydrophobic Ag NPs with high yield [39]. The Ag−OA (Figure 6c) and Ag−EOA (Figure 6d) thermogram showed two degradation steps at 175-320 • C and 320-750 • C that resemble OAm/OA mixture [40].…”
Section: Characterization Of the Modified Npsmentioning
confidence: 92%